ANALISIS KESETARAAN GENDER TERHADAP KEPUTUSAN INVESTASI SAHAM DI DANAREKSA SEKURITAS - Mahrifha Dheaanty; M. Faisal Abdhullah (Jurnal Ilmu Ekonomi JIE, 2020)
This study was conducted to analyze gender equality in stock investment decisions in Danareksa Securities, which are measured using financial factors (financial analysis and financial literacy) and non-financial factors (self-confidence and intuition) as independent variables and stock investment decisions as independent variables. This research uses a quantitative descriptive method. This research is conducted to study certain objects by distributing questionnaires which are then interpreted so that the results of the research and conclusions drawn merely describe (expose) a symptom of events as they really are. The results of this study indicate that there is a positive influence of the independent variables (intuition, financial analysis, financial literacy, and self-confidence) on investment decisions at Danareksa Sekuritas. However, the linear regression equation shows a significant value at a constant less than 0.05 so it cannot be used to predict.